ANALISIS 5S PADA PANTI ASUHAN MUSYTAMIRUL FURQON ROWOSARI TEMBALANG SEMARANG - Arsi Widiandari; Zaki Ainul Fadli; Dewi Saraswati; Maharani Ratna Patria; Nur Hastuti (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
One of the Japanese work culture that is widely applied in many countries is 5S (Seiri, Seiton, Siso, Seiketsu and Shitsuke ). 5S not only practice in company activity but also in life activity. In company especially at manufacturing industry, 5S practice will produce qualified product. Although 5S culture easy to understand and simple, but it is need a consistency and very difficult to be applied. Therefore, practice of 5S especially 5S habituations not only practice in company but also in many educational institution for example school, university and orphanage.